PERANCANGAN APLIKASI SISTEM PRESENSI KARYAWAN MENGGUNAKAN PENGENALAN WAJAH DI PT. MEDIA KREASI ABADI - Istia Budi; Sibarani, Gabriella Yunita (PROSIDING SEMINASTIKA, 2024)
Employee attendance is a crucial element in the human resource management of a company. PT. Media Kreasi Abadi as an innovative company engaged in IT (Information & Technology) Consultant services, Telecommunications, General Suppliers, Contractors, and Training (International Certified), understands the importance of efficiency in monitoring employee attendance. Therefore, this study aims to design and implement an employee attendance system application using facial recognition technology. The methodology used in this study is the Waterfall method by involving the stages of needs analysis, system design, implementation, and evaluation. Needs analysis is carried out by conducting a survey of the needs and expectations of employees and management of PT. Media Kreasi Abadi related to the attendance system. System design involves intuitive and efficient user interface design, as well as the integration of reliable facial recognition algorithms. This app is designed to create an easier, faster, and more accurate employee presence experience. The use of facial recognition technology is expected to overcome problems such as attendance fraud, loss of attendance cards, and improve the security of employee attendance data. During implementation, the application was tested in the real environment of PT. Media Kreasi Abadi by involving active employee participation. The evaluation results show that this application provides increased efficiency and accuracy of employee attendance. In addition, the positive response from users indicates a good reception to the implementation of facial recognition technology in the attendance system. Thus, designing an employee attendance system application using facial recognition at PT. Media Kreasi Abadi is expected to make a positive contribution to the company's operational efficiency and provide innovative solutions in employee attendance management.